2023
DOI: 10.3390/jcm12062357
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Training in Virtual Reality Improves Auditory Spatial Adaptation in Unilateral Hearing Loss Patients

Abstract: Unilateral hearing loss (UHL) leads to an alteration of binaural cues resulting in a significant increment of spatial errors in the horizontal plane. In this study, nineteen patients with UHL were recruited and randomized in a cross-over design into two groups; a first group (n = 9) that received spatial audiovisual training in the first session and a non-spatial audiovisual training in the second session (2 to 4 weeks after the first session). A second group (n = 10) received the same training in the opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An important aspect of testing monaural hearing or hearing in noise is the effect of training. Several authors have shown that the capacity of pure-tone azimuth localization improves with training [25][26][27]. A higher dependency on spectral cues and sensitivity central adjustment in the case of asymmetrical hearing [25] and enhanced spatial performances with the exploitation of visual cues [26] have been advocated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect of testing monaural hearing or hearing in noise is the effect of training. Several authors have shown that the capacity of pure-tone azimuth localization improves with training [25][26][27]. A higher dependency on spectral cues and sensitivity central adjustment in the case of asymmetrical hearing [25] and enhanced spatial performances with the exploitation of visual cues [26] have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that the capacity of pure-tone azimuth localization improves with training [25][26][27]. A higher dependency on spectral cues and sensitivity central adjustment in the case of asymmetrical hearing [25] and enhanced spatial performances with the exploitation of visual cues [26] have been advocated. Hearing performances in noise also improve with different types of training such as hearing in noise [27] conditions or even musical activities [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the experiment, all participants signed an informed consent document, which had received ethical approval from the national ethics committee in France (Ile de France X, N° ID RCB 2019-A02293-54) and registered as clinical trial (clinicaltrials.gov: NCT04183348). The present work focuses on the data collected in the context of a broader sound localization training protocol during the pre-training session only (full results are published in Valzolgher, Todeschini et al, 2022 ; Valzolgher, Gatel, et al, 2022 ; Valzolgher, Bouzaid, et al, 2023 ; and Alzaher et al, 2023 , for NH, bCI, uCI, and uHL participants, respectively). Although the sample size was determined by the research question of the training studies, it is noteworthy that the sample size in each of the groups matches the numerosity of a previous study that investigated a similar experimental question ( Pavani et al, 2017 , N = 17).…”
Section: Methodsmentioning
confidence: 99%
“…In a comprehensive analysis conducted in South Korea focusing on UHL and the use of hearing aids (HAs), researchers discovered that the decision to adopt HAs was influenced by the hearing threshold levels in both the better and worse ear [ 12 ]. The role of AT in UHL aural rehabilitation has been scarcely investigated in the literature, even though a recent preliminary report supports the effectiveness of specifically designed rehabilitation methods for this population of patients [ 13 ]. Phonak’s Roger Pen is an advanced remote microphone system featuring digital adaptive multi-channel technology, which wirelessly channels the speaker’s voice directly to the sound processor of an HA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%